Complete plastome sequence of Acorus tatarinowii (Acoraceae), a traditional Chinese medicinal plant from Xishuangbanna, Yunnan, China - Gong Yan-Xiong; Tian Yao-Hua; Nan Jiang; Wen-Bin Yu (Mitochondrial DNA. Part B. Resources, 2020)
The complete plastome of Acorus tatarinowii is 153,296 bp in length, with two long inverted repeats (25,752 bp for each) separating by a large single-copy (83,533 bp) and a small single-copy (18,240 bp). The plastome contained 112 unique genes, including 78 protein-coding genes, 30 transfer RNAs, and 4 ribosomal RNAs. Phylogenetic analyses showed that A. tatarinowii was closely related to A. gramineus.